REPRESENTASI NILAI MORAL PADA FILM PENDEK BAPAK KARYA PANIRADYA KAISTIMEWAN - Muhammad Shahrun Nizam; Anwari Anwari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Film as a communication media acts as an experience and conveyor of moral messages. A film presents a sign or code as a meaning in conveying a message. There are two formulations of the problem in this study, namely: (1) How is the denotative, connotative and mythical meaning in the short film